Faktor-faktor yang Mempengaruhi Kepuasan Kerja Perawat di Ruang Isolasi Covid-19 - Zainal Abidinsah; Ratna Wardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the factors that affect nurse job satisfaction in the Covid 19 isolation room. This research design uses quantitative observational, research approach using cross sectional analysis using multiple regression. The results showed that there was an effect of salary on nurse job satisfaction with a p-value of 0.061. In the promotion opportunity variable, the p-value is 0.000, which means that there is an effect of promotion opportunities on nurses' job satisfaction. In the supervision variable, the p-value is 0.002, which means that there is an influence of supervision on nurses' job satisfaction. Job satisfaction of nurses obtained in this study which significantly influenced was the opportunity for promotion and supervision, but the salary variable had no effect on nurses' job satisfaction. In conclusion, there is no effect of salary on nurses' job satisfaction, there is an effect of promotional opportunities on nurses' job satisfaction, the effect of supervision on nurses' job satisfaction. Keywords: Job Satisfaction, Promotion Opportunities, Salary, Supervision